Rancang Bangun Absensi Mahasiswa Berbasis Fingerprint Menggunakan Komunikasi Wireless - Mohamad Dimyati Ayatullah; Enes Ariyanto Sandi; Galih Hendra Wibowo (Jurnal Informatika: Jurnal Pengembangan IT, 2019)
The teaching and learning process on campus is always supervised by paying attention to attendance. Some campuses use this attendance as a condition for taking the exam. However, the attendance system is still manual, which is by using a signature on the attendance sheet. This system has several weaknesses which include the occurrence of fraudulent attendance, difficulty in monitoring attendance, and data that cannot be presented quickly. The study proposes an attendance system using fingerprints connected to wireless networks that are already available on campus. Wireless networks are used as a medium of communication between attendance tools and database servers. The use of wireless networks aims to facilitate equipment used in classrooms during the lecture process. Attendance tool designed on a single Raspberry Pi computer board that is equipped with fingerprint sensors, power banks and LCD screens. While wireless LAN devices are integrated in the Raspberry Pi boar. The attendance system begins with an enroll process to save the lecturer and student fingerprint templates. Each template is given an ID to be stored on the database server using TCP wireless and protocol networks. The enroll process observations require an average time of 4 seconds which consists of: transmission time and time identification of fingerprint characteristics to the creation of fingerprint templates. The attendance process in lecture activities begins with the absence of lecturers and is followed by students. The average time needed to do attendance is 4 seconds. During the data attendance process can transmit between the attendance device (client) and server. Through a fingerprint-based attendance device based on the available wireless network infrastructure in the campus, it can improve the efficiency of attendance monitoring in real time.